Supraparticles with a Magnetic Fingerprint Readable by Magnetic Particle Spectroscopy: An Alternative beyond Optical Tracers. Issue 9 (3rd June 2019) - Müssig, Stephan; Fidler, Florian; Haddad, Daniel; Hiller, Karl‐Heinz; Wintzheimer, Susanne; Mandel, Karl
Abstract: Marking and identification of materials is becoming increasingly important due to complex global resource and supply chains. Luminescent particle‐based markers have come to the forefront due to their small dimensions and their ability to be integrated in diverse materials. However, light‐absorbing materials can hardly be marked by these particles, thus leading to insufficient recycling rates of, e.g., black plastics. In this work, microparticles with a unique magnetic fingerprint are tailored by modification of their nanoparticle building blocks. This fingerprint tailoring is achieved either by combination of magnetic building blocks with nonmagnetic ones in the supraparticles or, alternatively, by surface modification of the building blocks. An easy‐to‐use device, based on the principle of magnetic particle spectroscopy (MPS), is established to resolve the magnetic fingerprint information. This facilitates the employment of magnetic supraparticles as markers for product tracking and identification. As a proof of concept, it is shown that such particles enable the marking of black plastic. Abstract : Magnetic microparticles, which carry a magnetic fingerprint, are presented. The fingerprint is adjustable by structural or compositional modification of their nanoparticle building blocks. An easy‐to‐use device based on magnetic particle spectroscopy resolves the defined signal even after incorporation of the particles into a black plastic. Therefore, this marking technology is an approach toward sorting and recycling of dark plastics.